Purification of Pyoverdines of Pseudomonas fluorescens 2-79 by Copper-Chelate Chromatography - Xiao, Rong; Kisaalita, William S. (Applied and environmental microbiology, 1995)
Three pyoverdines, Pf-A, Pf-B, and Pf-C, were purified with copper-chelate Sepharose and Sephadex G-15 columns from Pseudomonas fluorescens 2-79, and the yields (per 100 ml of culture supernatant) were 2.8, 21.6, and 3.2 mg, respectively. The absorption and fluorescence spectra of these pyoverdines were strongly pH dependent. Characteristic changes in the maximal absorbance wavelengths were observed when Fe(sup3+) or Cu(sup2+) was added. The addition of Cu(sup2+) shifted the pyoverdine Pf-B absorbance spectrum so that it exhibited a single peak at 410 nm but did not give rise to a new absorbance maximum at approximately 460 nm, which appeared when Fe(sup3+) was added. Fluorescence quenching experiments revealed that the forward reaction rate constant with pyoverdines was much higher with Cu(sup2+) (10(sup4) to 10(sup5) M(sup-1) s(sup-1)) than with Fe(sup3+) (10(sup2) M(sup-1) s(sup-1)). However, Cu(sup2+)-pyoverdine complexes were completely dissociated by EDTA at a low concentration (0.1 mM), while the level of Fe(sup3+)-pyoverdine complex dissociation at the same EDTA concentration was relatively low. The dissociation of Fe(sup3+)-pyoverdine complexes was EDTA concentration dependent. Formation of free pyoverdine was observed when the three types of Fe(sup3+)-pyoverdine complexes were incubated separately with P. fluorescens 2-79 cells, thus demonstrating that pyoverdines Pf-A, Pf-B, and Pf-C mediate iron transport.